The knowledge about food allergy among UiTM students (UiTM Terengganu, Dungun Campus) / Norhafizah Berahim and Noor Iszaiswa Arshad - Berahim, Norhafizah; Arshad, Noor Iszaiswa (2017)
The aim of this research was to determine the knowledge level of food allergy among UiTM students. This study only use quantitative research approaches which is one of the primary data collection method. A questionnaire was designed to measure the knowledge level of food allergy among the students. 200 questionnaires were distributed randomly to students in UiTM Terengganu, Dungun Campus. The results of this study will reveal the knowledge level and the awareness of food allergy among UiTM students. The findings provided a useful information and knowledge to the students and indirectly will make them more aware to the food allergy.